2016
DOI: 10.3390/molecules22010041
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Destruxin A on Relish and Rel Gene Regulation to the Suspected Immune-Related Genes of Silkworm

Abstract: Destruxin A (DA), a cyclodepsipeptidic mycotoxin of entomopathogenic fungus, Metarhizium anisopliae, has anti-immunity activity against insects, but the mechanism of immune regulation is not clear yet. In our previous experiment, the significant expression changes of Bm_nscaf2838_045, Bm_nscaf2674_066, and Bm_nscaf2767_133 genes in a silkworm’s hemocytes were found, which suggested that these genes might be involved in insect’s innate immunity. In the current experiment, the silkworm cell line Bm12 was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…bassiana as well as B . brongniartii are known to produce several of these compounds [ 52 ]. Whether any of these bioactive compounds are directly affecting these immune signaling pathways in the mosquito remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…bassiana as well as B . brongniartii are known to produce several of these compounds [ 52 ]. Whether any of these bioactive compounds are directly affecting these immune signaling pathways in the mosquito remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For this, it is necessary to elucidate the targets of DA acting on insects. In the past decade, several studies indicated that DA changes the morphology of hemocytes and brings on equilibrium chaos of intra-and extra-cellular hydrogen and calcium ion in Bombyx mori [4,5], and regulates immune related gene expression [6,7]. Recently, a few DA binding-proteins in silkworm were found [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This complex has been shown to have a role in pre-messenger RNA splicing from yeast to humans. Previously, we found that DA influences the splicing of pre-mRNA of silkworm’s immune-related gene, BmRelish, and results in expression of BmRelish1 which is higher than that of BmRelish2 [11]. Therefore, we hypothesized that DA might interfere with the interaction of BmPPI with Bmo.3174 and lead to irregularity splicing of the downstream immune-related gene in the immune-related pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DA has attracted attention for its immunosuppressant activity. It has been reported that DA impacts antimicrobial peptides in Drosophila melanogaster [10], regulates the gene expression of BmRelish and BmRel of the Imd pathway in Bombyx mori [11], and influences the expression of immunity-related genes in insects [12,13,14]. However, there has been no significant progress on clarifying the molecular toxicology of DA.…”
Section: Introductionmentioning
confidence: 99%